Unia Wolności w Oświęcimiu - Urbiński, Jacek (Wydawnictwo Uniwersytetu Rzeszowskiego, 2014)
The Freedom Union was a liberal democratic political party based on the Solidarity trade union movement. It was founded in 1994 out of the merger of the Democratic Union and the Liberal Democratic Congress. The leaders of The Freedom Union had a huge influence on policy in free and democratic Poland. In 2001 some members of the party decided to move to join the new Civic Platform. In 2005 the Freedom Union’s leadership founded the social-liberal Democratic Party. The article is about The Freedom Union in Oswiecim, where the party was authentic in power.
THE FREEDOM UNION IN OŚWIĘCIM
Keywords: Freedom Union; political party; power; Oświęcim